Technical Management Impact Assessment Wastewater Against Health Problems in Sanitarian Workers at Hospital X With A Life Cycle Analysis (LCA) Approach - Miftakhul Nurdiyanto; Tri Joko; Mursid Raharjo (International Journal Labs, 2025)
Hospital wastewater, laden with organic, microbial, and chemical contaminants, poses significant environmental and occupational health risks. Despite regulations, gaps persist in integrated assessment and mitigation strategies. This study evaluates the environmental and health impacts of wastewater management at Hospital X using LCA, identifying hotspots in energy use, chemical toxicity, and worker exposure. A mixed-methods approach combined LCA (SimaPro 9.0, ReCiPe 2016 Midpoint) with surveys of 33 sanitarian workers. Data included WWTP performance metrics, effluent quality, and health complaints. The WWTP (100 m³/day) exceeded capacity (105 m³/day), with aeration (45% of GHG emissions) and chlorine use (20% human toxicity) as key hotspots. Health surveys revealed 85% of workers suffered respiratory/skin issues, correlating with LCA-identified exposure risks. The study underscores the need for capacity expansion (?300 m³/day), automation (sludge handling), and renewable energy integration, offering a model for sustainable hospital wastewater management in Indonesia.